In the Jewish tradition : a year of foods and festivities - Fellner, Judith B. (New York : Smithmark, 1995)
Provides information about the origins and meanings of different Jewish holidays, including Rosh Hashanah, Yom Kippur, Hanukkah, Purim, Passover, Shavuot, and Sukkot, and features a selection of recipes, songs, prayers, and stories associated with each celebration.
Rosh Hashanah -- Yom Kippur -- Sukkot, Shemini Atzeret, and Simhat Torah -- Hanukkah -- Purim -- Passover -- Shavuot.
Includes index.
Keywords: Fasts and feasts -- Judaism; Holiday cooking; Jewish cooking